Optimizing the Effectiveness of Students’ Health Communication Through Information Sources and Learning Factors - Susie Sugiarti; Anisti; Rosmalia Ahmad (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The integration of communication processes occurs when conventional and digital communication patterns are used simultaneously, allowing communication activities to take place both face-to-face and through mediated channels. This condition has become increasingly relevant as the need for health information grows more dynamic and is obtained from diverse sources. This study aims to analyze the direct effect of information sources on learning factors and the effectiveness of health communication, the direct effect of learning factors on the effectiveness of health communication, and the indirect effect of information sources on the effectiveness of health communication through learning factors. The main concepts examined in this study include information sources, learning factors, and health communication effectiveness. This research employed an explanatory quantitative approach involving 97 students from Grade X and XI at SMA Sejahtera 1 Depok City. Data were collected through a survey using a Google Form questionnaire and analyzed using multivariate analysis. The results indicate that information sources have a direct and significant effect on both learning factors and the effectiveness of health communication. Learning factors also have a direct and significant effect on the effectiveness of health communication. However, learning factors do not mediate the relationship between information sources and health communication effectiveness. Future studies are recommended to involve a larger sample size and adopt a mixed-methods approach to allow for comparative analysis, such as multi-group analysis.